Modification of Structural Phase State and Mechanical Properties of Poly-Grained Titanium Alloy Implanted by Aluminum Ions; IOP Conference Series: Materials Science and Engineering; Vol. 112 : Fundamental Aspects of Rare-earth Elements Mining and Separation and Modern Materials Engineering (REES-2015) - Nikonenko A. V.; Popova N. A.; Nikonenko E. L. Elena Leonidovna; Kalashnikov M. P. Mark Petrovich; Kurzina A. (2016, 2016)
Title screen